In situ hydrogenation of C59N and resonant electron capture of C59NHx (x=0, 1 and 5) - Vasil’ev, Yu; Abzalimov, R.; Tuktarov, R.; Nasibullaev, Sh.; Hirsch, Andreas; Taylor, Roger; Drewello, Thomas (Chemical Physics Letters, 2002)
The hydrogenation of the aza[60]fullerene CN· has been studied in situ. The CN· monomer is formed by thermal evaporation and dissociation of the (CN) dimer and is hydrogenated in the heated inlet channel of a mass spectrometer, which is used subsequently for the product analysis. In addition to the expected formation of CNH, the abundant production of CNH is observed. Increasing the availability of hydrogen for the reduction enhances the formation of CNH, which is eventually obtained as the main product. The effective yield curves of the negative ions CNH, where x = 0, 1 and 5 are detailed and contrasted with the ion yields of CH, where x = 0, 2 and 6. It is found that increasing hydrogen attainment reduces the energy range in which long-lived molecular ions can result from electron capture. © 2002 Elsevier Science B.V. All rights reserved.